Alumina Supported Synthesis of Some α,β– Unsaturated Heterocyclic Acids - Mishra, A. D. (Journal of Nepal Chemical Society, 2013)
Solid supported synthesis of some novel 3- (5'- substituted-2-furyl/thienyl) propen -2- oic acids has been carried out from malonic acid and 5- substituted furan/thiophene-2-carboxaldehydes under microwave irradiations in solvent free condition. The reaction completed in one step via condensation affording 88-96% of yield within 4-6 minutes. The reactions are accompanied with easy work-up, limited use of organic solvents and the use of inexpensive and hazard- free chemicals. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9229 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 1-4 Uploaded date : 12/3/2013